EKSISTENSI MUHAMMADIYAH DI TENGAH TANTANGAN ZAMAN - Muchamad Suradji; Romelah Romelah; Moh. Nur Hakim (LPPM UNISDA, 2023)
Abstract: The purpose of this study is to determine the existence of the Muhammadiyah Movement in facing the challenges of the times. This research is included in the type of library research. The data sources used in this study come from the documentation that includes books, journals, articles, and so on related to the topic under study. The analysis technique used is descriptive analysis, which describes the sub-topic of research and then analyzes it to get research conclusions. The results of the study can be described that Muhammadiyah as a movement organization does have a fundamental role to play. This can be seen from Muhammadiyah's proselytizing, in general, is renewal. The identity of the Muhammadiyah movement includes the Islamic movement, the tajdid movement, the indictment movement, the multi-faceted indictment and the Islamization charges. The existence of the Muhammadiyah Movement in facing the challenges of the times is internal and external, on a local, national, and international scale. However, Muhammadiyah, in its proselytizing, always conveys to the community or people that those facing the challenges of the global world must be ingenious, have full awareness, unshakable faith, strong will and hard work. The Muhammadiyah movement, in the form of proselytizing, is a charitable effort to establish educational institutions, hospitals, etc. Muhammadiyah offers a more humanism-prophetic path to civilization so that the people with greedy passions do not destroy their civilization.